PWE-085 Analysis of new patient attendances for nafld at three london hospitals highlights the need to develop clinical risk stratification pathways. (22nd June 2015) - Srivastava, A; Gailer, R; Gulati, S; Warner, A; Morgan, S; Sennett, K; Suri, D; Thorburn, D; Tsochatzis, E; Rosenberg, W
Abstract : Introduction: 30% of the UK population has NAFLD. A significant minority (10%) will have NASH of whom 15% will develop cirrhosis. Recognising this subpopulation at risk can be difficult as patients are often asymptomatic. Non-invasive tests (NIT) of liver fibrosis including FIB4 and the Enhanced Liver Fibrosis (ELF) panel have been validated in NAFLD and provide opportunities to devise risk stratification pathways. We reviewed GP referrals with a final diagnosis of NAFLD to three London hospitals to assess the potential role of NIT in new pathways. Method: All new GP referrals to the Royal Free, Whittington and University College London hospitals with a final diagnosis of NAFLD between 1/4/12 and 31/3/13 had their electronic records assessed. Demographic, clinical, laboratory and outcome data were collected. The potential impact of the use of FIB4 was evaluated. Prospectively FIB4 and ELF are being used to stratify patients prior to referral. Results: Over 1 year, 191 patients with a final diagnosis of NAFLD were referred by GP's. 130 had sufficient data to calculate FIB-4 values. 87 patients (67%) had FIB4 <1.30 (low risk of advanced liver disease) and no liver related events were documented. 3 patients [2%] had FIB4 >3.25 (high risk of advanced liver disease). FIB4 was indeterminate (1.30–3.25) in 40 (31%) who would be stratified with ELF in the new pathway (Figure 1) . Twenty (15%) had a liver biopsy. 10 (8%) had FIB4 <1.30, each of whom had a histological stage of ≤F2 fibrosis and could have avoided referral under the new pathway. Of 7 (5%) with confirmed cirrhosis on biopsy, two had FIB4 >3.25 and 5 had indeterminate FIB4 scores (1.30–3.25). Conclusion: New approaches to tackle the increasing burden of NAFLD are required. Patients at low risk of advanced fibrosis should have their risk factors managed in primary care, whilst those at high risk need specialist input. Existing methods are ineffective in stratifying patients. Applying FIB4, 67% of referrals could have been avoided but the majority of cirrhotic patients would not have been identified. We have initiated a novel primary care pathway integrating the use of FIB4 and ELF (to categorise FIB-4 indeterminate cases) to stratify patients for management in primary or secondary care. Within the 1st year, over 400 patients have entered the pathway and data from clinical and cost effectiveness analysis are due in mid 2015. Disclosure of interest: None Declared.